Effects of Dendrobium nobile on antioxidant capacity, hormone levels, testicular metabolism, and reproductive performance of aged roosters - Depeng Zhao; Yushi Shi; Xia Long; Qisong Tan; Jinlin Yang; Hui Li (PLoS ONE, 2025)
Oxidative stress is a major cause of semen quality decline in old roosters. Dendrobium nobile Lindl (DNL), a Chinese herbal medicine, exhibits excellent antioxidant activity. Therefore, the present study aimed to investigate the effects of dietary DNL supplementation on semen quality, antioxidant capacity, reproductive hormone levels, and testicular tissue structure in aged roosters. This study further aimed to elucidate the potential mechanism for improving reproductive performance. Thus, the expression of antioxidant defense system-related genes was verified, and metabolomic analysis was performed. Twenty 56-week-old recessive, white-feathered roosters were randomly assigned into two groups. The DNL group was fed a basal diet supplemented with 2500 mg/kg DNL for 60 days, whereas the control group was fed a basal diet. Here, DNL improved the semen quality (sperm density and motility) and antioxidant capacity of aged roosters, increased the expression of genes in the Nrf2 pathway, increased serum hormone levels, and delayed testicular tissue degradation. Seventy-six differential metabolites that are mainly enriched in amino acid biosynthesis pathways, taurine and hypotaurine metabolism, and cysteine and methionine metabolism were identified. DL-serine, DL-cysteine, and α-ketoglutarate were related to improved testicular antioxidant capacity. In this study, dietary supplementation with 2500 mg/kg DNL delayed the decline in reproductive performance by improving the antioxidant capacity of aging roosters. These findings could facilitate the use of DNL as a feed additive to improve the reproductive performance of aged roosters.